PB28, the Sigma-1 and Sigma-2 Receptors Modulator With Potent Anti–SARS-CoV-2 Activity: A Review About Its Pharmacological Properties and Structure Affinity Relationships - Abate, Carmen; Niso, Mauro; Abatematteo, Francesca Serena; Contino, Marialessandra; Colabufo, Nicola Antonio; Berardi, Francesco (Frontiers in Pharmacology, 2020)
These unprecedented times have forced the scientific community to gather to face the COVID-19 pandemic. Efforts in diverse directions have been made. A multi-university team has focused on the identification of the host (human) proteins interacting with SARS-CoV-2 viral proteins, with the aim of hampering these interactions that may cause severe COVID-19 symptoms. Sigma-1 and sigma-2 receptors surprisingly belong to the “druggable” host proteins found, with the pan-sigma receptor modulator PB28 displaying the most potent anti–SARS-CoV-2 activity in in vitro assays. Being 20-fold more active than hydroxychloroquine, without cardiac side effects, PB28 is a promising antiviral candidate worthy of further investigation. Our research group developed PB28 in 1996 and have thoroughly characterized its biological properties since then. Structure–affinity relationship (SAfiR) studies at the sigma receptor subtypes were also undertaken with PB28 as the lead compound. We herein report our knowledge of PB28 to share information that may help to gain insight into the antiviral action of this compound and sigma receptors, while providing structural hints that may speed up the translation into therapeutics of this class of ligands.